Investigation of sea level anomalies related with NAO along the west coasts of Turkey and their consistency with sea surface temperature trends - Dogan, Mustafa; Cigizoglu, H. Kerem; Sanli, D. Ugur; Ulke, Asli (SPRINGER WIEN, 2015)
It is well-known that North Atlantic Oscillation (NAO), which is one of the large-scaled climate modes effective in the Northern Hemisphere, has a considerable affect on the water resources and climatic indicators especially in the Mediterranean basin. In recent years, also crucial studies about the sea level rise in relation to climate change have been accelerated. Turkey has about 20 modernized tide gauge stations equipped with permanent GPS receivers and targets to contribute to global sea level rise studies in the future. The aim of this study is to find out the effects of North Atlantic Oscillation on the national shores using the data of four tide-gauge stations located on the Aegean and Mediterranean coasts of Turkey. Implications from these four tide gauges would motivate researches to take into account the effect of NAO in calculating the true sea level rise at the national coasts. While studying the sea level changes, vertical crustal movement has been observed using the data of tide gauge GPS stations, and this situation has been taken into consideration in the evaluation of sea levels. Besides, in order to investigate the influences of thermal expansion on sea levels, sea surface temperature data of the meteorology stations near the tide gauges have been evaluated. The homogeneity of the data sets was analyzed using four statistical tests. As a result, all of the meteorology stations' temperature series and tide gauges' data are subjected to trend detection after the homogeneity analysis. Eventually, the effects of North Atlantic Oscillation on both sea levels and sea surface temperatures have been introduced. The study results indicate high correlation between North Atlantic Oscillation and the sea level and sea surface temperature events. It is seen that the linear correlation between the sea level trends of the considered stations and the sea surface temperature data of the related meteorology stations is considerably significant.
Keywords: SOUTH CHINA SEA; BLACK-SEA; INTERANNUAL VARIABILITY; REGIME SHIFTS; RISE; ALTIMETRY; IMPACT; Meteorology & Atmospheric Sciences